DRAMATURGI DIBALIK KEHIDUPAN SOCIAL CLIMBER - Wiratri Anindhita (Jurnal Komunikasi dan Bisnis, 2018)
Life is like a two parts of coins, which every part of life has a front stage and a back stage. This study purpose to know about how the front stage side of social climber, the back stage side of social climber, and how the experience as a social climber. This study uses dramaturgy theories. In dramaturgy study will be seen about the difference in actorâ€™s behavior while on the frontstage and backstage. Concepts that used in this research is social climber and social media. This research uses qualitative descriptive research method. Data collection through in depth interview with informant, non-participant observation, and literature study. Data analysis techniques in this research using data analysis techniques from Miles and Huberman. The result of this study, actually the three of informan were not came from rich family that have a high economic status. If they are in front stage side, they will show a very good performance, like wearing many branded things. But, if they are not in the front stage side, they will be preferring to do many things of homework, wearing a simple clothes, not wearing a branded product, and also do the activity like a normal student.Â Key words: dramaturgy, social climber, social media